Steel structures analysis and design for vibrations and earthquakes : based on Eurocode 3 and Eurocode 8 - Ghosh, Karuna Moy (Whittles Publishing ; Distributed in North America by CRC Press, 2011)
'Steel Structures' analyses the behaviour of two steel framed structures and their structural elements subjected to complex dynamic forces under the actions of earthquake motions and vibrations due to dynamic forces created by the effects of an unbalanced rotating mass of machines.
Keywords: Steel framing (Building) -- Earthquake effects.; Steel framing (Building) -- Vibration.; Earthquake resistant design.; elektronické knihy; electronic books